2009
DOI: 10.5194/bg-6-2383-2009
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemistry of a low-activity cold seep in the Larsen B area, western Weddell Sea, Antarctica

Abstract: Abstract. First videographic indication of an Antarctic cold seep ecosystem was recently obtained from the collapsed Larsen B ice shelf, western Weddell Sea (Domack et al., 2005). Within the framework of the R/V Polarstern expedition ANTXXIII-8, we revisited this area for geochemical, microbiological and further videographical examinations. During two dives with ROV Cherokee (MARUM, Bremen), several bivalve shell agglomerations of the seep-associated, chemosynthetic clam Calyptogena sp. were found in the troug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 75 publications
1
53
0
Order By: Relevance
“…Wallmann et al, 1997Wallmann et al, , 2006Suess et al, 1998;Tryon et al, 1999;Sahling et al, 2008;Niemann et al, 2009;Reitz et al, 2011). The upward supply of hydrocarbons towards and across the sediment/water interface produces steep geochemical gradients of pore water constituents, and typically stimulates high rates of anaerobic oxidation of methane (AOM) and other hydrocarbons with sulfate as an electron acceptor close to the sediment surface (Borowski et al, 1996;Treude et al, 2003).…”
Section: Fischer Et Al: Pore Water Geochemistry Of Cold Seeps Offmentioning
confidence: 99%
See 3 more Smart Citations
“…Wallmann et al, 1997Wallmann et al, , 2006Suess et al, 1998;Tryon et al, 1999;Sahling et al, 2008;Niemann et al, 2009;Reitz et al, 2011). The upward supply of hydrocarbons towards and across the sediment/water interface produces steep geochemical gradients of pore water constituents, and typically stimulates high rates of anaerobic oxidation of methane (AOM) and other hydrocarbons with sulfate as an electron acceptor close to the sediment surface (Borowski et al, 1996;Treude et al, 2003).…”
Section: Fischer Et Al: Pore Water Geochemistry Of Cold Seeps Offmentioning
confidence: 99%
“…Numerous studies have demonstrated that the flux of methane and sulfide towards the sediment/water interface determines the microbial and faunal community composition at cold seeps (e.g. Dando and Hovland, 1992;Barry et al, 1997;Sibuet and Olu, 1998;Sahling et al, 2002;Levin et al, 2003;Treude et al, 2003;van Dover et al, 2003;Arvidson et al, 2004;Levin, 2005;Niemann et al, 2006;Niemann et al, 2009;Lichtschlag et al, 2010a).…”
Section: Fischer Et Al: Pore Water Geochemistry Of Cold Seeps Offmentioning
confidence: 99%
See 2 more Smart Citations
“…Such microbial mats are typical for active cold seeps where the anaerobic oxidation of methane leads to high sulphide concentrations near the sediment surface [8], [21]. An additional sign of cold-seep activity was present in the form of small mounds encrusted by bivalve shells belonging to the seep-associated vesicomyid clam Calyptogena sp., which lives in symbiosis with sulphur-oxidising bacteria [22].…”
Section: Introductionmentioning
confidence: 99%